Analisis Materi Bahasa Perancis Pada Buku Édito B1 - Methode de Francais - Shafira Widihardjo; Farida Amalia; Iis Sopiawati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
Analysis of French language textbooks is still limited, the restricted accessibility of textbooks in Indonesia as reference resources for studying French is the cause of this obstacle. Meanwhile, the availability of these textbooks is very much needed, both by teachers and learners. The purpose of this research on the Édito B1-Méthode de Français book is to examine the completeness of the content profile and identity of this book and analyze the content of French language materials based on the standards established by CECRL. The purpose of this study is to provide insight on the textbook's applicability as a resource for instructors and students pursuing French at the B1 level